17α-ethinylestradiol and 4-tert-octylphenol concurrently disrupt the immune response of common carp. Issue 107 (December 2020) - Maciuszek, Magdalena; Pijanowski, Lukasz; Pekala-Safinska, Agnieszka; Palichleb, Paulina; Błachut, Michał; Verburg-van Kemenade, B.M. Lidy; Chadzińska, Magdalena
Abstract: The aquatic environment is massively polluted with endocrine-disrupting compounds (EDCs) including synthetic estrogens (e.g. 17α-ethinylestradiol, EE2) and alkylphenols (e.g. 4- tert- octylphenol, 4 t -OP). A major mechanism of action for estrogenic EDCs is their interaction with estrogen receptors and consequently their modulation of the action of enzymes involved in steroid conversion e.g. aromatase CYP19. We now studied the effects of EE2 and 4 t -OP on the anti-bacterial immune response of common carp. We investigated effects on the number/composition of inflammatory leukocytes and on the gene expression of mediators that regulate inflammation and EDC binding. In vitro we found that high concentrations of both EE2 and 4 t -OP down-regulated IFN-γ2 and IFN-γ-dependent immune responses in LPS-stimulated monocytes/macrophages. Similarly, during bacterial infection in fish, in vivo treated with EE2 and 4 t -OP, decreased gene expression of il-12p35 and of ifn-γ2 was found in the focus of inflammation. Moreover, during A. salmonicida -induced infection in EE2-treated carp, but not in fish fed with 4 t -OP-treated food, we found an enhanced inflammatory reaction manifested by high number of inflammatory peritoneal leukocytes, including phagocytes and higher expression of pro-inflammatory mediators ( inos, il-1β, cxcl8_l2 ). Furthermore, in the liver, EE2 down-regulated the expression of acute phase proteins: CRPs and C3. Importantly, both in vitro and in vivo, EDCs altered the expression of estrogen receptors: nuclear ( erα and erβ ) and membrane ( gpr30 ). EDCs also induced up-regulation of the cyp19b gene. Our findings reveal that contamination of the aquatic milieu with estrogenic EDCs, may considerably violate the subtle and particular allostatic interactions between the immune response and endogenous estrogens and this may have negative consequences for fish health. Highlights: High concentration of EE2 and 4t-OP down-regulate in vitro IFN-γ-dependent immune responses. During bacterial infection in EE2 in vivo enhances inflammatory reaction. Water contamination with estrogenic EDCs have negative consequences for fish health.